อิทธิพลของอัตราส่วนสารละลายธาตุอาหารและน้ำหมักมูลไส้เดือนดินต่อการเจริญเติบโตของผักกาดหอมพันธุ์กรีนโอ๊คที่ปลูกในระบบไฮโดรพอนิกส์ - ศิริงาม, ธนภูมิ; บุญมี, นราศักดิ์; พงษ์ประยูร, วาสินี (Thai Journal of Science and Technology, 2019)
Abstract Lettuce (Lactuca sativa L.) is a typical salad vegetable which has high nutrition and economic value. Currently, this plant species was mostly cultivated in the hydroponic system in order to control the factor affecting the growth and yield. In the present, the liquid vermicomposts were compromised with nutrient solution in the hydroponics system. Therefore, this research aims to investigate the influence of Phranakhon nutrient solution formula and vermicompost ratio on growth of lettuce var. green oak cultivated in hydroponics system. The experimental design was arranged in completely randomized design (CRD) with five replications. The results showed that the lettuce var. green oak cultivated with Phranakhon nutrient solution formula and vermicompost ratio at 100:0 % (v/v) showed the highest of the leaf number, plant canopy, root fresh weight, root dry weight, root dry matter, shoot fresh weight, shoot dry weight and shoot dry matter. Keywords: lettuce; nutrient solution; liquid vermicompost; hydroponic